1982
DOI: 10.1525/ae.1982.9.1.02a00070
|View full text |Cite
|
Sign up to set email alerts
|

the domain of emotion words on Ifaluk

Abstract: Internal feeling states have commonly been assumed to be the primary referents of emotion words in Western thought, both social-scientific (Cardiner, Metcalf, and Beebe-Center 1937; Solomon 1976Solomon , 1978 and lay (Davitz 1969). In these views, the function of the emotion word is to label an internal state and perhaps to communicate that state to others. To an important extent, however, scientific conceptions of emotion and person are rooted in In these societies, emotion words are seen as statements about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0
23

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(158 citation statements)
references
References 20 publications
1
128
0
23
Order By: Relevance
“…For example, research on the organization and structure of the emotion lexicon has generally indicated substantial cross-cultural commonalities and only more subtle variations in the organization of that domain (see Russell, 1991, for an excellent review). Close crosscultural correspondence is often obtained for at least one ofthe major dimensions (pleasure-displeasure being the strongest organizational feature found among emotion words) but not the others in multidimensional scaling of the words (Herrmann & Raybeck, 1981;Lutz, 1982;Russell, 1983;Russell et al, 1989). Thus, it appears that when the folk psychologies regarding both cognition and affect are taken into account, both cross-cultural commonalities and variations can be found in the ways that human beings construe the mind, although the particular insights vary from domain to domain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research on the organization and structure of the emotion lexicon has generally indicated substantial cross-cultural commonalities and only more subtle variations in the organization of that domain (see Russell, 1991, for an excellent review). Close crosscultural correspondence is often obtained for at least one ofthe major dimensions (pleasure-displeasure being the strongest organizational feature found among emotion words) but not the others in multidimensional scaling of the words (Herrmann & Raybeck, 1981;Lutz, 1982;Russell, 1983;Russell et al, 1989). Thus, it appears that when the folk psychologies regarding both cognition and affect are taken into account, both cross-cultural commonalities and variations can be found in the ways that human beings construe the mind, although the particular insights vary from domain to domain.…”
Section: Discussionmentioning
confidence: 99%
“…Emotion has attracted growing attention from anthropologists, but has remained conceptually subordinate to cognition. Emotions have been defined as cognitive by making methodological choices to study them through essentially cognitive card-sorting tasks (Lutz 1982), by focusing on the culturally provided schemata for dealing with them (Levy 1973), or by defining them explicitly as interpretations constituted of concepts, beliefs, attitudes, and desires (Solomon 1984). A step toward the present position was taken by Rosaldo (1984), who suggested that emotions are a kind of cognition with a greater "sense of the engagement of the actor's self, .…”
Section: Collapsed Dualities: Psychological Anthropology and T H E Bomentioning
confidence: 99%
“…Dont les principaux défenseurs sont Armon-Jones, 1986a et b ; Averill, 1980Averill, , 1986Greenwood, 1992a et b ;Harré, 1986 ;Lutz, 1982Lutz, , 1986Lutz et White, 1986. 15. Certains constructionnistes soutiennent que la fonction des émotions est la régulation des comportements indésirables et la promotion des attitudes qui reflètent et endossent les pratiques religieuses, politiques et sociales d 'une communauté (Armon-Jones, 1986b).…”
Section: Constructionnisme Socialunclassified